(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
This article analyzes the scientific and pedagogical foundations of environmental education for children in preschool educational institutions. The content, goals, and objectives of environmental education, as well as its implementation methods and forms, are examined from both theoretical and practical perspectives. The role of educators, game-based learning, observation, and experimental activities in shaping children’s conscious attitudes toward nature is substantiated. The article also presents conclusions and practical recommendations for developing environmental culture in preschool children.